Recurrent hip dislocations in a child with congenital insensitivity to pain with anhidrosis ( CIPA) syndrome: a case report. - Alananzh, Mohammad; Al-Halasa, Fares; Al-omari, Jamal A.K; Alkhreisat, Mohammad (Journal of Neonatal Surgery, 2025)
congenital insensitivity to pain with anhidrosis ( CIPA) syndrome is a rare autosomal recessive disease, with children affected presenting with frequent musculoskeletal manifestations. In this case report we present the case of a 4 years old female child with recurrent hip dislocation, which is managed conservatively with closed reduction and bracing. The child continues to have spontaneous dislocations that can be reduced at home.This case discuss the challenges dealing with dislocated hips and potential sequela of Charcot joint